Referent-individual: A theoretical outline to think about crime and consumer culture in Brazilian youth - Melo, P. B.; Assis, R. V. (Um novo olhar para cultura, comunicação e informação, 2023)
Classical and contemporary studies on communication means highlight the influence of the media and social media on the development of beliefs and attitudes of individuals. When we think about media discourses – entertainment, advertising and journalistic narratives -, we perceive that it is possible to propose concept review and new meaning to social facts from these narratives. Exposure to the media has a relevant role to intervene on the ways of seeing and thinking about things of the world, operating both as an objective and subjective dimension of the actor. In a general way, individuals are vulnerable to the persuasive process on the media narratives because their positions come from lenient observants of a persistent publicity which defines acceptable behavior, social distinction conditions and elements that incorporate to individuals, giving meaning to their identitiesin the socialstructure. Beyond that, media representations assume an active role of social control, stability and change, showing – on the social media, journalistic, soup opera, cinematographic or entertainment narratives – the various versions of being an individual-in-search-for-distinction: through cars, clothes, through the shaped body and the objects linked to this human being.